Reporting the Delta: An Exploration of Climate, Space, and Society Through Archival Documentaries - Iuorio, Luca; Arbara, Sophia; Champlin, Carissa (2025)
The Dutch delta tells the story of constant struggle, resistance and negotiation between land, water, and people. It is always in motion - from fluctuating tides and historic floods to flows of global trade and engineering mega works.In Reporting the Delta, archival documentaties by, among others, Bert Haanstra, Louis van Gasteren, and George Sluizer are used as tools to investigate the transformations of the Dutch delta. These films capture the ambition of reshaping nature and mastering water's movements and serve as points of departure for a broader exploration.Through essays, interviews, and visual digests, Reporting the Delta weaves together voices from science, art, and design. The book offers a visual and narrative reflection on the entangled forces of technology, climate, and daily life, resulting in a compelling journey through a delta in a constant state of adaptation.